“Estudio de pre -Factibilidad para la instalación de una planta procesadora de snack, maíz (Zea mays) arroz (Oryoza sativa), en el distrito de la banda de shilcayo – Reción San Martín - Dávila Pezo, Dante (2011)
St. Martin in the region has a very important production area for rice and corn, capable of supplying cereals listed, to produce snack of 8 and 35 grams per bag for the regional market consumption, the raw material is within the plant location Agroindustry, REGION SAN MARTIN has 49.912 hectares of rice lurid, with a production of 310.848 MT and 52134 hectares planted with yellow corn, producing over 104,711 MT Currently snack products made with different flavors come from the line with different presentations of weight, according to the survey conducted in the city of Tarapoto in the present study found a snack consumption of 51, 151 kg I person I year. The potential demand unmet annually at an estimated 16,080.17 REGIONAL TM annual share of 5. 72% is being met by 94.28 with snack products from the coast. let raises the production of 460.800 T.M. Snacks from A and B in the first year, then increased to 645. 120 TM A YB-type snack in the second year in which occurs 70% of installed capacity to 100% in the third year and thereafter shall be considered a production of 921.600 MT per year. The maquila and equipment required for the production process are taken into the domestic market, though the characteristics consistent with the registered capacity in the theoretical calculations, suggesting the location of the ago-industrial plant in SHILCAYO BANDA, this place meets the first priority. The physical infrastructure requirements of the processor will, of which 2.000 m2 706.04 m2 deal to build the plant. The total investment amounts to U.S. $ 373,653.72 of which $ 295,043.90 will be used for tangible fixed investment for deferred investments $ 14,472.82 and $ 64, 137.00 for working capital. Total investments of $ 373,653.72 the 70.83% will be financed by the line PROPEMCAFCOFIDE through private banks as debt, with a rate of 14% and a repayment period of 5 years with a grace year. Devise an investment schedule for preoperational stage, over a period of 6 months to enter the seventh month after the operative stage with a production of 460.800 kilograms of snacks a year, equivalent to 50% of installed capacity and net income of $ 37,946.7. The unit cost of production of snack for the presentation of 8 g. is$ 0.016 and 35 g. price is$ 0.07 and sales with a profit margin of 50%, for submission of 8 g. is$ 0.024 and 35 g. is $ 0.105 per bag. Standard rates of economic and financial! evaluation shows the feasibility of carrying out the project for an opportunity cost of 21.08% per annum of dollars invested there is a positive FNPV VANE and n TIRE 64% 81% TIRF both indicates an adequate return on internal! rate of return and economic benefit cost ratio of 1.14 and financial! Cost Benefit of 2.28, the result indicates a high economic return of 17%. The total investment of $ 373,653.72 recovered over period of 2 years, 3months and 14 dais.